2022
DOI: 10.1186/s12944-022-01709-8
|View full text |Cite
|
Sign up to set email alerts
|

FGF15 promotes hepatic NPC1L1 degradation in lithogenic diet-fed mice

Abstract: Background Cholesterol gallstone disease (CGD) is accompanied by biliary cholesterol supersaturation. Hepatic Niemann-Pick C1-like 1 (NPC1L1), which is present in humans but not in wild-type (WT) mice, promotes hepatocyte cholesterol uptake and decreases biliary cholesterol supersaturation. In contrast, intestinal NPC1L1 promotes intestinal cholesterol absorption, increasing biliary cholesterol supersaturation. Ezetimibe (EZE) can inhibit both hepatic and intestinal NPC1L1. However, whether hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…It was demonstrated that the FGF15-FGFR4 axis induced by cholic acid promotes the ubiquitination of hepatic NPC1L1 [ 20 ]. Meanwhile, FGF15 released by the intestine inhibits bile acid synthesis in the liver by reducing Cyp7a1 transcription through FGFR4 and SHP [ 37 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was demonstrated that the FGF15-FGFR4 axis induced by cholic acid promotes the ubiquitination of hepatic NPC1L1 [ 20 ]. Meanwhile, FGF15 released by the intestine inhibits bile acid synthesis in the liver by reducing Cyp7a1 transcription through FGFR4 and SHP [ 37 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…We modulated liver-specific gene expression by AAV-mediated gene transfer method [ 20 ]. The murine NPC1L1 cDNA sequences from GenBank (No.…”
Section: Methodsmentioning
confidence: 99%